Dregs of Cardamine hupingshanensis as a feed additive to improve the egg quality - Yu, Feike; Yu, Xiaohan; Liu, Rongchen; Guo, Dawei; Deng, Qian; Liang, Bingbing; Liu, Xiaoye; Dong, Hong (Frontiers in Nutrition, 2022)
Natural plant herbs have many active compounds to prevent poultry diseases and improve the poultry products. However, most herbs are supplied for human medicine. Thus, for economic and sustainable development purposes, the dregs of Cardamine hupingshanensis (DCH) was developed as a feed additive improve egg quality of laying hens in this work. Results showed that the contents of selenium in hen serum and eggs were increased under DCH feeding. Subsequently, DCH also promote the antioxidant capacity and immunity of laying hens though the increasing of superoxide dismutase (SOD), catalase (CAT) and immunoglobulin G (IgG) by ELISA detection. Finally, production performance and egg quality were further graded by monitoring the produce condition and scoring the indexes of egg quality, which also displayed that DCH as feed additive significantly improved the egg quality by enhancing yolk color, eggshell thickness and egg shape index.